Inhibiting breast cancer by targeting the thromboxane A2 pathway - Haitao Li (Nature Portfolio, 2017)
Breast cancer: Pathway target identified The identification of a signaling pathway connected to the progression of breast cancer could prove a valuable therapeutic target. The breast cancer treatment tamoxifen, although successful, is limited to certain tumor types, and so the search is on to pinpoint molecular targets that are ubiquitous across breast cancers. Zigang Dong at the University of Minnesota, US, and co-workers identified that the thromboxane A2 (TXA2) pathway is highly-expressed in human breast tumors and premalignant lesions. Further examination showed that TXA2 is crucial for tumor cell growth and metastasis. When the researchers knocked-out TXA2 production in mouse models, this suppressed both the formation and spread of tumors. The team advise caution because TXA2 is also required for wound healing and other key processes, although short-term bursts of pathway suppression may be an option for breast cancer therapy.